Effect of the position of the internal reflectors on the thermal operation of a solar cooker box-type. Issue 1 (January 2021) - Terres, H; Chávez, S; Lizardi, A; Alvarez, E
Abstract: The results of the effect that five internal reflectors have on the operation of a box-type solar cooker are shown. Variations in the angular position of the reflectors generate new dimensions for the cooker. For this reason, in order to carry out the comparison of four solar cookers with different dimensions under the same operating conditions, it is used the numerical simulation that allows obtaining the representative temperatures that describe the thermal operation of the solar cooker. The temperature values achieved and expressly referred to the heating of 1 liter of water are obtained from the numerical solution of a mathematical model under initial conditions. The results show that for a tilt of the reflector angles with respect to the horizontal of 40°, 50°, 60°, 70° and 81° the highest values of the water temperature are obtained, specifically, the highest value among these is 98.1 ° C. While for reflector inclinations of 13°, 18°, 21°, 24° and 30°, there are the lowest temperature values and among these, the highest value is 83.9 °C. The results, together with their discussion, contribute to the knowledge of the behavior of the components of box-type solar cookers.